The Costs and Profitability of Tobacco Compared to Other Crops in Zimbabwe - Keyser, John C. (World Bank, Washington, DC, 2013)
This study compares the financial costs and returns to tobacco growing with twelve (traditional and non-traditional) alternative crops, looking at profitability, costs, labor intensity, financial support, technical infrastructure, land-suitability, marketing difficulties, world demand, and production risks. It aims to provide an improved understanding of the trade-offs farmers face in deciding what crops to grow. The analysis is based on an original set of 91 production budgets estimated in January 2001 specifically for this study. The study finds that tobacco is a highly profitable cash crop for both large and small farmers. however even if global demand for tobacco were to fall significantly in the future, the impact on employment and the broader economy would depend on the extent to which commercial farmers were able to switch to other high value export crops. Changes in Zimbabwe's land policy in 2001/2002 are likely to have a much larger impact on tobacco growing and exports and on the economy than demand-induced changes in the global market for tobacco.